Cascade Greinacher : Desain dan Simulasi Penaik Tegangan Output DC Menggunakan Modifikasi Rangkaian Cascade - Agung Fitrahadi; Mulyadi, Adi; Mas Ahmad Baihaqi (Journal Electric Field, 2024)
This paper discusses the design and simulation of the Cascade Greinacher circuit to increase the dc output voltage and current. The voltage increasing circuit using the Cockroft-Walton method has a large output voltage ripple and voltage drop. Meanwhile, half wave and full wave rectifier circuits are only capable of producing a DC output voltage and do not reach the maximum voltage value. In addition, the load resistance at each input power saturation is different and high frequencies require the addition of a capacitor circuit. Therefore, the Greinacher Doubler Circuit (GDC) rectifier is proposed with a modified diode and capacitor series arranged in nine levels in parallel. The circuit modification is used as a DC output voltage rectifier to reduce output voltage ripple. Then the circuit modification was tested by simulating the PSIM software and varying input voltages. Simulation testing uses a 220 volts voltage source, 50 Hz frequency, and component specifications for a single-phase step-down transformer 220 to 12 volts, 8 diodes (DXN, DN/DXN1, DN1/DXN2, DN2/DXN3, DN3), 8 capacitors with 4700Uf value (CXN, CN/CXN1, CN1/CXN2, CN2/CXN3, CN2), and 100 Ω resistor. simulation results which produce a voltage greater than 3 times the input voltage, namely 35.7 V and a current of 0.98 A. Even though at times 0.001 seconds and 0.0035 seconds and 0.0054 seconds the output voltage and current are constant at 4.9 volts respectively, the current is 0.03 A, current 0.08 A and current 0.013 A. The output voltage Vout, Vs and current continue to increase when it reaches 1 second.